Specific deficits in visual electrophysiology in a mouse model of dominant optic atrophy. - Barnard, A; Charbel Issa, P; Perganta, G; Williams, P; Davies, V; Sekaran, S; Votruba, M; Maclaren, R (2011)
Autosomal dominant optic atrophy (ADOA) is a slowly progressive optic neuropathy caused by mutations in the OPA1 gene. OPA1 is ubiquitously expressed and plays a key role in mitochondrial fusion. Heterozygous Opa1 mutant mice (B6; C3-Opa1(Q285STOP)), have previously been reported to develop visual defects and optic nerve changes. In this study, in vivo visual electrophysiological testing (ERGs and VEPs) was performed on 11-13 month old B6; C3-Opa1(Q285STOP) mice (n = 5) and age/sex matched wildtype littermate controls. Full intensity series were recorded in response to brief (4 ms) single flash stimuli delivered in a Ganzfeld dome under dark- and light-adapted conditions. The major ERG components (a-wave and b-wave) showed no detectable difference from wildtype in the amplitude or implicit time of dark-adapted ERGs across the full intensity range tested. This was also true for the components of the dark-adapted VEP. However, the light-adapted ERG responses revealed a significant reduction in the photopic negative response (PhNR) amplitude in Opa1(+/-) animals relative to wildtypes at the brighter intensities tested. Elements of the light-adapted VEP were also abnormal in mutant mice. Overall Opa1(+/-) mice display functional deficits in electrophysiology that are consistent with ganglion cell dysfunction. These deficits may correlate with a reduction in the dendritic arborisation of retinal ganglion cells, which has been previously reported to occur at a similar age in the same mutant mouse line (Williams et al., 2010). The functional phenotype we have described in this mouse model may be useful in the robust and accurate assessment of potential treatments for ADOA.